Life Determining Practices of Professions: The Case of Banker Truck Driver - Onur Uca (Journal of Economy Culture and Society)
Professions which determine the income, status, living conditions and retirement life are one of the most important areas of research within social sciences. This article focuses on the formation of the daily life bythe professions through the investigation of two professions that are very different from each other. The first one is banking and the second is truck driving. In this context, the research firstly dealt with the history of work and the transformation of work in the modern era. Then, the banking profession, its life shaping practices and the ways it can define the individuals were explored in detail. Subsequently, the truck driving profession, the life style it accompanies and how it shapes the social lives of people were explained. It was revealed that the professions determine the formation of the value worlds of people. People pursuing different professions also have different worlds of value. Finally, in order to illustrate how this happens in daily life, the relationship between daily life, professions and values is clarified in the last part of the research.